2010
DOI: 10.1038/onc.2010.465
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-93 promotes tumor growth and angiogenesis by targeting integrin-β8

Abstract: It has been reported that the miR-106bB25 cluster, a paralog of the miR-17B92 cluster, possesses oncogenic activities. However, the precise role of each microRNA (miRNA) in the miR-106bB25 cluster is not yet known. In this study, we examined the function of miR-93, one of the microRNAs within the miR-106bB25 cluster, in angiogenesis and tumor formation. We found that miR-93 enhanced cell survival, promoted sphere formation and augmented tumor growth. Most strikingly, when miR-93-overexpressing U87 cells were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
242
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(253 citation statements)
references
References 39 publications
10
242
1
Order By: Relevance
“…The miR-93 gene is located on chromosome 7q22.1, it can suppress proliferation and differentiation of cancer stem cells, while promoting tumor growth and malignant cells survival (Fang et al, 2011;Yu et al, 2011;Suling et al, 2012). In the present study, mir-93 expression was 5.29 fold higher compared to normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-93 gene is located on chromosome 7q22.1, it can suppress proliferation and differentiation of cancer stem cells, while promoting tumor growth and malignant cells survival (Fang et al, 2011;Yu et al, 2011;Suling et al, 2012). In the present study, mir-93 expression was 5.29 fold higher compared to normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Other downregulated putative targets were found to be involved in cytokine interaction and cellular adhesion, strengthening the evidence for involvement of these miRNAs in adhesion, including the integrin pathway (31). miR-17-92 has been shown to inhibit collagen synthesis by targeting TGFbR2, in mice (32), as well as it is known that miR-93 promotes angiogenesis and tumor growth by targeting integrinb8 (33), and together with mir-106a, seems to directly target the Cofilin2 gene (34).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, increasing studies have demonstrated that several miRNAs take part in the processes of angiogenesis and they play crucial roles in the progress or prognosis of cancers such as hepatocellular carcinoma, human colon cancer, and bladder cancer 20, 21, 22. For example, in a study conducted by Fang et al,23 miR‐93 represses integrin‐β8 expression, thereby allowing spreading of endothelial cells, and consequently promotes angiogenesis in glioma. It is also revealed that miR‐126 facilitates angiogenesis of GC through regulating vascular endothelial growth factor (VEGF) level, which is an important regulator in vasculogenesis 18.…”
Section: Discussionmentioning
confidence: 99%